Prevalence and Prognosis Impact of Patient–Ventilator Asynchrony in Early Phase of Weaning according to Two Detection Methods. (December 2017) - Rolland-Debord, Camille; Bureau, Côme; Poitou, Tymothee; Belin, Lisa; Clavel, Marc; Perbet, Sébastien; Terzi, Nicolas; Kouatchet, Achille; Similowski, Thomas; Demoule, Alexandre
Abstract : Background: Patient–ventilator asynchrony is associated with a poorer outcome. The prevalence and severity of asynchrony during the early phase of weaning has never been specifically described. The authors' first aim was to evaluate the prognosis impact and the factors associated with asynchrony. Their second aim was to compare the prevalence of asynchrony according to two methods of detection: a visual inspection of signals and a computerized method integrating electromyographic activity of the diaphragm. Methods: This was an ancillary study of a multicenter, randomized controlled trial comparing neurally adjusted ventilatory assist to pressure support ventilation. Asynchrony was quantified at 12, 24, 36, and 48 h after switching from controlled ventilation to a partial mode of ventilatory assistance according to the two methods. An asynchrony index greater than or equal to 10% defined severe asynchrony. Results: A total of 103 patients ventilated for a median duration of 5 days (interquartile range, 3 to 9 days) were included. Whatever the method used for quantification, severe patient–ventilator asynchrony was not associated with an alteration of the outcome. No factor was associated with severe asynchrony. The prevalence of asynchrony was significantly lower when the quantification was based on flow and pressure than when it was based on the electromyographic activity of the diaphragm at 0.3 min –1 (interquartile range, 0.2 to 0.8 min –1 ) and 4.7 min –1 (interquartile range, 3.2 to 7.7 min –1 ; P < 0.0001), respectively. Conclusions: During the early phase of weaning in patients receiving a partial ventilatory mode, severe patient–ventilator asynchrony was not associated with adverse clinical outcome, although the prevalence of patient–ventilator asynchrony varies according to the definitions and methods used for detection. Abstract : In 103 patients, asynchrony was assessed every 12 h after switching from full to partial ventilator support. Asynchrony was not associated with adverse outcome, and its incidence was less if monitoring airway pressure (or flow) patterns compared with electrical activity of the diaphragm.Supplemental Digital Content is available in the text.